A gest??o educacional de uma institui????o de ensino p??blica da esfera federal: o caso do Col??gio Militar de Bras??lia - Souza, Gabriela Menezes de (2017)
This research has as general objective to identify the model of educational management employed in the CMB from the official documents that govern the teaching in the institution and from the perception of the participants of the research. This is a case study about the Military College of Bras??lia (CMB), a public institution of the federal sphere, whose main sponsor is the Brazilian Army. Participating in the research were a manager of the Directorate of Preparatory Education and Assistance (DEPA), the Teaching Director, the pedagogical advisor to the Head of the Teaching Division (DE), the Head of School Supervision and six former CMB students, as well as teachers and educational supervisors. Also analyzed were documents that deal with all activities related to the development and operation of military colleges belonging to the Military College System of Brazil (SCMB). In these normative documents, it was noticed the concern with the diverse dimensions of the school. They are texts that act as support for the activities of the manager, since they guide all the work to be developed in the college. As theoretical reference, theoretical ideas were used that deal with concepts of management of educational institutions, educational management models, educational planning concepts and models of such planning as Ribeiro (1978), L??ck (2000), Zainko (2000) ), Sander (2007), Kuenzer et all (2015), among others. After analyzing the data, it is considered that the management model adopted by the CMB follows a hierarchical structure that can be noticed in the way the analyzed documents are organized. The results show that the management model assumed by the CMB contemplates traces of a strategic planning and allows, in a limited way, the participation of the school community. We therefore consider that the management model applied by CMB is close to the multidimensional paradigm of Sander (2007), since it contemplates the different dimensions in which a school should be managed, except for the dimension of the participation of the school community.